Kebijakan Inaktif terkait Pendidikan Seks di Indonesia: Studi Kasus di Aceh dan Yogyakarta (Jurnal Nawala Politika, 2022)
There has been a long silence in Indonesia’s education system and policy on whether schools should establish clear sexuality education policies. Although there was an advancement of the brand-new Decree of Minister of Education named Permendikbud no 30/ 2021 on the Prevention of Sexual Harassment at Educational Institution, it has been ambiguous whether the state urge schools to prevent such by establishing a sexuality education policy. I argue that this policy inaction leads to drawbacks for the state’s policy on body and sexuality. This paper uses a literature review to structure some concepts on social policy and the complexity of sex-related issues. It conducts a literature review as a method as well, to serve some understanding of two cases in Aceh and Yogyakarta and explores similarities and differences across the cases. Finally, the discussions offer a few points on the intended and unintended effects of the policy inaction, which are seen through some perspectives on child protection, power struggle, and rights approach.